ASSESSMENT OF THE FUNCTIONAL TYPES OF BODY MOBILIZATION BASED ON A DYNAMIC ANALYSIS OF SPECTRAL INDICATORS OF HEART RATE VARIABILITY AND THEIR CLASSIFICATION - Nevoit, G.V.; Potiazhenko М.М.; Mintser О.P. (World of Medicine and Biology, 2020)
The article is dedicated to the blessed memory of the hrv method and the cybernetic model of dual-circuit regulation of cardiac activity author Roman Markovich Baevsky (August 3, 1928 - May 31, 2020.) The article is devoted to the study of electromagnetic phenomena of human cardiac activity and the possibilities of their clinical use in practical medicine to assess the level of health in order to prevent NCDs. The results of a dynamic analysis of the spectral parameters of cardiac activity during the performance of an orthostatic test by functionally healthy people are given in the article. The authors described four functional types of mobilization/adaptation, gave a characterization and interpretation to them, proposed a variant of their classification based on the cybernetic model of dual-circuit regulation of cardiac activity R.M. Baevsky.